PENGUKURAN KINERJA BANK PEMBIAYAAN RAKYAT SYARIAH DENGAN PENDEKATAN MASLAHAH PERFORMA (MaP) (Studi pada BPRS Bangun Drajat Warga Yogyakarta) - Nur Faizah; Amimah Oktarina (Jurnal Ilmiah Ekonomi Islam, 2023)
Measurement of Maslahah Performance (MaP) has three advantages, namely: First, it focuses on the balance of all aspects of maslahah, namely religion (al-din), soul (al-nafs), descent (al-nasl), reason (al-aqal), and property (al-maal). BPRS BDW is one of the BPRS that has the highest assets and the highest net profit when compared to BPRS in DIY. The purpose of this study is first to describe the performance of BPRS Bangun Drajat Warga Yogyakarta using the Maslahah Performance (MaP) approach, secondly to measure and analyze the maslahah performance of BPRS Bangun Drajat Warga Yogyakarta using the Maslahah Performance (MaP) approach. The type of research used to compose this research is a type of field research (Field Research) with a normative-sociological approach. Informants in this study were stakeholders related to the implementation of maslahah performance, namely BPRS BDW employees with positions at the level of senior staff to Division heads, sharia supervisory board (DPS), and customers of BPRS Bangun Drajat Warga Yogyakarta. The data analysis technique used maslahah performance (MaP). MaP performance measurement is carried out using two methods, namely the measurement of benefit performance (result oriented) and benefit (process oriented) performance measurement. The results of this study are that the first BPRS BDW has implemented maslahah performance by fulfilling worship orientation, internal process orientation, talented workforce orientation, learning orientation, customer orientation, wealth orientation based on several strategic goals, measures, formulas, targets and strategic initiatives. Second, the performance measurement of Performance Problems in BPRS BDW is carried out by calculating the performance of the MaSC results and the performance of the MaSC process. BPRS BDW has a maslahah performance of 0.391, which means that BPRS BDW has provided benefits to all stakeholders. BPRS BDW has a maslahah process performance of 0.400, this figure shows that BPRS BDW has implemented a benefit performance system although not all have been implemented.